Technological opportunities and challenges for singapore logistic firms - Ee, Man Hoi (Nanyang Technological University, 2021)
The shaping of the current logistic industry in Singapore was triggered by the development of technological solutions to support productivity. The evolution of technology is structuring how logistic firms work and how the business is done. Logistic firms that realized technological trends and opportunities can explore potential value on their business. However, there are also technological challenges that may stop some logistic firms from adopting technological solutions. This report used methods that involved the literature review of public sources and interviews with members in logistics firms and technological solutions providers. The combination of information revealed that some technological trends and opportunities have been recognized and adopted in Singapore logistic firms such as automated warehouses, RFID, robotic, smart glasses, drones, vision systems, and 3D printing. Meanwhile, the common technological challenges have been discussed by participants in the interviews, including the concerns on the costs of adopting technologies and the traditional mindset of the industry to resist the adaptation to new technologies.